(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: This study aimed to describe outcomes and evaluate the quality of life in patients after rhinoplasty surgery. Subjects and Method: This prospective study was conducted on 52 patients who underwent rhinoplasty at Hanoi Medical University Hospital between April 2023 and April 2024. Clinical symptoms and quality of life were assessed using the SF-36 tool. Results: Among the 52 patients, 50 (96.2%) were female. Significant improvements were observed in nasal obstruction scores, which decreased from 2.67±0.47 pre-surgery to 0.65±0.68 at 6 months post-surgery (p<0.05). Facial pain and rhinitis scores also significantly improved at 1 and 6 months post-surgery (p<0.05). Quality of life, measured by the SF-36, showed marked improvement across all factors at both 1 and 6 months after surgery (p<0.05). Conclusion: Rhinoplasty significantly improved clinical symptoms, appearance, and quality of life, with the SF-36 serving as a reliable measure of surgical success.